The tears of the Rajas : mutiny, money and marriage in India 1805-1905 - Mount, Ferdinand, 1939- (Sydney : Simon & Schuster, A CBS Company, 2015)
The Tears of the Rajas is a sweeping, epic history of the British in India, seen through the experiences of a single family, the Lows, ancestors of the author, Ferdinand Mount, and also of Prime Minister David Cameron. When he was growing up, Ferdinand Mount used to wonder what stories the various Indian artefacts his family possessed from the days of the British rule of India could tell. Many years before, his Aunt Ursie had written a family history of the Lows of India which was largely ignored by the family. When the story of the Lows recently hit the headlines after it transpired that these same relatives were those of David Cameron, and that they were responsible for a number of atrocities in India, Ferdinand Mount set out to uncover the truth behind their lives. What emerged was an evocative, intense and thrilling history of 19th century British rule in India. Vividly and poignantly capturing the lives of one family, Mount tells the story of some of the most dramatic and terrible moments of the Indian Raj, from the mutinies, battles, massacres and famines, to the ineptitude, folly and sometimes deviousness of British rulers themselves. An epic history, full of stories of love, war, treachery and intrigue, Tears of the Rajas will surely become one of the classics of its kind
First published: 2015
Includes bibliographical references and index
Keywords: Lows family; India -- History -- British occupation, 1765-1947; History